THE MEDICINE OF THE FUTURE AND NEW TECHNOLOGY IN DENTISTRY - Alla Igorevna Karachunova; Svetlana Aleksandrovna Kalashnikova (Современная наука и инновации)
A new approach and a high level of professional dentist will now be not only in the ability to positively affect patient behavior and possession of clinical skills. It is also important to be aware of medical innovations in the field of dentistry, master new technologies and be able to provide high-quality high-tech help, be aware of the innovations in the ield of medicine of the future. All of the above will contribute to the establishment in Russia of a competitive market of dental services.